Perkembangan Kompetensi Absolut PTUN Beserta Problematikanya: Analisis Menurut UU PTUN dan UU No. 30 Tahun 2014 tentang Administrasi Pemerintahan - Nasution, Agus Nardi (Judex Laguens, 2023)
Absolute competence is the authority of the State Administrative Court to adjudicate a case according to the object, material or subject matter of the dispute. The development of this Law is seen by differences in legal concepts and the existence of PTUN dispute objects regulated in the UUAP where procedural law has not been accommodated in the Law. -State Administrative Court Law (UUPTUN). The research method used is normative law in which legal norms, legal concepts, legal principles and legal ideology are the research objects. This study uses 2 (two) types of approaches, namely the statutory approach relating to the State Administrative Court and the historical approach regarding the existence of the State Administrative Court. In Indonesia, with the enactment of the UUAP, it has contained fundamental changes in the previous regulations, which are contained in the contents of the UUPTU. The problem of absolute competence of PTUN after the implementation of UUAP in handling PTUN disputes no longer recognizes individual elements in administrative decisions by judges. Whereas the provisions contained in Article 87 of Law Number 30 of 2014 concerning Government Administration have contained hidden changes in the provisions of Article 1 number 9 of Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning Administrative Justice Country.